Evaluation of GABA Receptors of Ventral Tegmental Area in Cardiovascular Responses in Rat - Minoo Rasoulpanah; Fathmeh Kharazmi; Masoumeh Hatam (Iranian Journal of Medical Sciences, 2015)
Background: The ventral tegmental area (VTA) is well known for its role in cardiovascular control. It is demonstrated that about 20-30% of the VTA neurons are GABAergic though their role in cardiovascular control is not yet understood. This study is carried out to find the effects of GABA A and GABA B receptors on cardiovascular response of the VTA. Methods: Experiments were performed on urethane anesthetized male Wistar rats. Drugs were microinjected unilaterally into the VTA. The average changes in mean arterial pressure (MAP) and heart rate (HR) were compared between the case and the control groups using t test and with the pre-injection values using paired t test. Results: Microinjection of muscimol, a GABAA agonist (500, 1500 and 2500 pmol/100nl) into the VTA had no significant effect on MAP and HR compared with the saline group and pre-injection values. Injection of bicuculline methiodide (BMI, 100 and 200 pmol/100 nl), a GABAA antagonist, caused a significant increase in the MAP (11.1±1.95mmHg, P<0.5) and a decrease in HR (-32.07±10.2, P<0.01). Microinjection of baclofen a GABAB receptor agonist (500 or 1000 pmole/100 nl) and phaclofen a GABAB receptor antagonist (500 or 1000 pmole/100 nl) had no significant effects on MAP and HR. Conclusion: For the first time it was demonstrated that GABA system of the VTA inhibits the cardiovascular system through the activation of GABAA but not the GABAB receptors.